Mottled Water Hyacinth Weevil Neochetina eichhorniae Warner (Insecta: Coleoptera: Curculionidae) - Eutychus Kariuki; Carey Minteer (EDIS)
Sometimes referred to as the ‘mottled water hyacinth weevil’, Neochetina eichhorniae Warner is a weevil that attacks the invasive, aquatic plant, water hyacinth, Eichhornia crassipes (Mart.) Solms. Water hyacinth is considered one of the most destructive plants in aquatic ecosystems in the United States and, as a result, is listed in both the federal noxious weed list and Florida’s list of prohibited aquatic plants. Neochetina eichhorniae is host specific and causes substantial damage to water hyacinth, making it a valuable biological control agent for this invasive weed in many parts of the world. The insect was first introduced into the United States from Argentina in 1972, when scientists released the insect in Broward County, Florida, to manage water hyacinth (Perkins 1973). Since then, the insect has been introduced in more than three dozen countries worldwide (Winston et al. 2014). Post-introduction studies indicate the insect substantially suppresses the growth of water hyacinth, significantly reducing biomass, flowers production, and water surface coverage (Grodowitz et al. 1991, Center et al. 1999, Tipping et al. 2014, Nesslage et al. 2016) and the need for herbicide applications (Haag 1986).